Evaluating antirheumatic treatments using synovial biopsy: a recommendation for standardisation to be used in clinical trials. Issue 3 (24th November 2010) - van de Sande, Marleen G H; Gerlag, Danielle M; Lodde, Beatrijs M; van Baarsen, Lisa G M; Alivernini, Stefano; Codullo, Veronica; Felea, Ioana; Vieira-Sousa, Elsa; Fearon, Ursula; Reece, Richard; Montecucco, Carlomaurizio; Veale, Douglas J; et al.
Abstract : Inflammation of synovium is one of the hallmarks of rheumatoid arthritis (RA). Analysis of synovial tissue has increased our understanding of RA pathogenesis, aided in identifying potential therapeutic targets and has been used in the response and mechanistic evaluation of antirheumatic treatments. In addition, studies are ongoing, aimed at the identification of diagnostic and prognostic biomarkers in the synovium. This paper outlines the currently used procedures for sampling and processing of synovial tissue, and presents a standardised recommendation to support multicentre translational research.